2021
DOI: 10.1097/ncq.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Care Interactions and Clinical Outcomes in Black Versus White Nursing Home Residents With Dementia

Abstract: Background: With the increase in Black nursing home residents, racial and ethnic disparities in quality of care have been raised. Purpose: The purpose of this study was to evaluate racial disparities in care and outcomes over 12 months. Methods: This was a secondary data analysis using data from the Evidence Integration Triangle for Behavioral and Psychological Symptoms of Dementia study. A total of 553 residents, 24% Black residents and 76% White residents, from 55 nursing homes were included. Results: Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Black and Hispanic American older adults were more likely to be admitted to for‐profit facilities 74 and facilities that scored lower on quality indicators including rates of hospital readmission 56,74 . However, one study examined a variety of quality‐of‐care indicators and found mixed results 76 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black and Hispanic American older adults were more likely to be admitted to for‐profit facilities 74 and facilities that scored lower on quality indicators including rates of hospital readmission 56,74 . However, one study examined a variety of quality‐of‐care indicators and found mixed results 76 …”
Section: Resultsmentioning
confidence: 99%
“… 56 , 74 However, one study examined a variety of quality‐of‐care indicators and found mixed results. 76 …”
Section: Resultsmentioning
confidence: 99%